Chrysanthemum yantaiense, a rare new species of Asteraceae from China - Chen, Jun-Tong; Zhong, Jian; Shi, Xue-Jun; Zhang, Qi-Xiang; Sun, Ming (Phytotaxa, 2018)
In this paper, a rare new species of the genus Chrysanthemum from China, C. yantaiense, is described and illustrated. It appears most closely related to C. indicum, but its characters are quite different in stem habit, leaf, synflorescence, capitula size and chromosome ploidy. The diagnostic characters of the new species were proven in four years of observations in cultivation.